2009
DOI: 10.1186/1471-2407-9-176
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CXCR4 expression in hepatocellular carcinoma patients increases the risk of bone metastases and poor survival

Abstract: BackgroundThe chemokine and bone marrow-homing receptor CXCR4 is implicated in metastases of various cancers. This study was conducted to analyze the association of CXCR4 expression with hepatocellular carcinoma (HCC) bone metastasis and patient survival.MethodsTumor tissue from HCC patients with (n = 43) and without (n = 138) bone metastasis was subjected to immunohistochemical staining for CXCR4 using tissue microarrays. Immunoreactivity was evaluated semi-quantitatively. A receiver-operating characteristic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 29 publications
4
83
0
2
Order By: Relevance
“…The immunohistochemistry protocols are described elsewhere (13)(14)(15). Primary antibodies were mouse antihuman monoclonal antibodies against hypoxia-inducible factor-1a (HIF-1a), VEGF (Santa Cruz Biotechnology), and matrix metalloproteinase-2 (MMP-2; R&D Systems).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The immunohistochemistry protocols are described elsewhere (13)(14)(15). Primary antibodies were mouse antihuman monoclonal antibodies against hypoxia-inducible factor-1a (HIF-1a), VEGF (Santa Cruz Biotechnology), and matrix metalloproteinase-2 (MMP-2; R&D Systems).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…A tissue microarray (TMA) was constructed as described previously (13)(14)(15). H&E-stained slides were screened to identify optimal intratumoral and peritumoral tissue for analysis.…”
Section: Tissue Microarraymentioning
confidence: 99%
“…Its expression is elevated in breast cancer and leukemia (13). Previous studies have reported that CXCR4 expression in hepatocellular carcinoma (HCC) might correlate with the progress of the cancer and its lymphatic and distant metastasis (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Different tumor types have distinct chemokine receptor expression profiles, with CXCR4 and CCR7 extensively investigated (3). Notably, CXCR4 is widely expressed in at least 23 different cancer types including HCCs and is associated with more aggressive disease and poorer patient prognosis (3,9,10). The CXCL12-CXCR4 axis is therefore of particular importance in cancer metastasis and currently represents the top target for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%